Mechatronics and Precision Livestock Farming in Mexican Animal Production - Negrete, Jaime Cuauhtemoc (Animal Review, 2017)
For México, the base projection shows that the demand for this meat grows at rates faster than the production, reason why an increase in the imports in the long term is expected. The base projection shows that purchases abroad will reach a level close to 390 thousand tons in 2018.In Mexico, the deficit in the milk market is complemented by imports. For 2009, an import of 1.0 billion liters is estimated and in 2018 these are hoped to fall to 946 million liters [1]. According to these projections makes it necessary to analyze the pressure for increased food production of animal origin, leading to review technologies applied in the rest of the world to carry out such an increase, a technology is the application of mechatronics to animal production, which is also known as livestock farming precision. Being the objective of the present article the revision of the state of the art in the world and in Mexico of this technology. In Mexico it is possible to increase the productivity of Livestock Farming, if the decision to guide and formed human capital and training are taken at all three levels ; Bachelor , Masters and Ph D , to the research and application of livestock mechatronics, results in developed countries so it evidence Mexico cannot be left behind in this regard , besides that is the only way to increase food production, applying mechatronics in animal production .So previously treated the perspectives for the precision animal production in the country are very big.